2022
DOI: 10.3390/ijms23063317
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Polycystic Kidney Disease: From Pathophysiology of Cystogenesis to Advances in the Treatment

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic renal disease, with an estimated prevalence between 1:1000 and 1:2500. It is mostly caused by mutations of the PKD1 and PKD2 genes encoding polycystin 1 (PC1) and polycystin 2 (PC2) that regulate cellular processes such as fluid transport, differentiation, proliferation, apoptosis and cell adhesion. Reduction of calcium ions and induction of cyclic adenosine monophosphate (sAMP) promote cyst enlargement by transepithelial fluid sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 103 publications
0
15
0
5
Order By: Relevance
“…21,22 Advances in the understanding of the genetic basis of PKD have led to the investigation of various upstream targets of cystogenesis, including vasopressin-2 receptor (AVPR2), EGFR/ErB2, Beta-1 integrin receptor, and c-SRC. [23][24][25] It is unknown whether heterozygotes of ALG8 PTVs would benefit from tolvaptan although tolvaptan is typically indicated only for patients with elevated total kidney volume using the Mayo imaging classification (Mayo Class 1C, 1D, 1E). 22,26,27 While we did not have uniform imaging to calculate Mayo imaging classification on patients, we found that kidneys were not enlarged for the vast majority of the ALG8 PTV heterozygotes so most in our study would not qualify from tolvaptan.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Advances in the understanding of the genetic basis of PKD have led to the investigation of various upstream targets of cystogenesis, including vasopressin-2 receptor (AVPR2), EGFR/ErB2, Beta-1 integrin receptor, and c-SRC. [23][24][25] It is unknown whether heterozygotes of ALG8 PTVs would benefit from tolvaptan although tolvaptan is typically indicated only for patients with elevated total kidney volume using the Mayo imaging classification (Mayo Class 1C, 1D, 1E). 22,26,27 While we did not have uniform imaging to calculate Mayo imaging classification on patients, we found that kidneys were not enlarged for the vast majority of the ALG8 PTV heterozygotes so most in our study would not qualify from tolvaptan.…”
Section: Discussionmentioning
confidence: 99%
“…With a high penetrant state, affecting between 1:400 and 1:1000 live births, ADPKD is the most common inherited kidney disease. The bilateral kidney cysts that characterize ADPKD continuously grow and develop, inducing progressive renal enlargement and increasing the total kidney volume (TKV), frequently complicated by hypertension, polyuria, nocturia, discomfort, nephrolithiasis, hematuria, infections, kidney function loss, and ESRD which typically manifests at age 55 [ 27 , 28 ]. Even within families, disease severity and course might vary considerably.…”
Section: Adpkdmentioning
confidence: 99%
“…There was a total of 1,550 DEGs including 786 upregulated and 764 downregulated genes in Pkd1-KO kidneys compared with wildtype (Figure 7E). Hallmark analysis identified several signaling pathways known to be involved in cystogenesis and fibrosis in ADPKD (Figure 7F), including TNFα-NF-κB, TGFβ, JAK-STAT, and KRAS signaling 67,68 . Subsequently, we compared the DEGs from the Cep120-KO and Pkd1-KO mice at P15 (Figure 7G).…”
Section: Transcriptional Profiling Of Cep120 Fibrocystic Kidneys Impl...mentioning
confidence: 99%